Adolescent pregnancy in Zimbabwe: distribution by socio-demographic factors. - Siziya, S.; Rusakaniko, S.; Marufu, T.; Matchaba -Hove, Reginald; Mudyarabikwa, O.; Gwanzura, L. (2016)
We conducted a further analysis of the Zimbabwe 1994 demographic health survey data to determine demographic and social factors associated with adolescent pregnancies in Zimba notbwe. Out of a total of 1486 female adolescents sampled, 12 did not provide information on whether they had begun child bearing, and were therefore excluded from the analysis. Significantly elevated odds ratios (OR) were noted for age (OR=2.27,95% confidence interval (CI) 2.01-2.58) and having primary or no education (OR=1.58, 95%CI 1.35,1.87). Watching television every week was protective (OR=0.69, 95%CI 0.57-0.83). Heads of households with less than 25 years of age were 2.10 (95%CI 1.54-2.87) times more likely to have adolescents who were pregnant when compared with heads of households of age 35 years or more. We conclude that electronic media should be continued to be used to deliver sex education messages to adolescents in order to curb the adolescent pregnancy epidemic.